P832 Is there an association between pain severity and vitamin D deficiency in IBD?. (16th January 2018) - Frigstad, S O; Høivik, M; Jahnsen, J; Cvancarova, M; Grimstad, T; Berset, I P; Huppertz-Hauss, G; Hovde, Ø; Torp, R; Bernklev, T; Moum, B; Jelsness-Jørgensen, L -P
Abstract: Background: Pain is commonly reported in IBD patients, and evidence suggests a multifactorial aetiology. Vitamin D deficiency is known to cause muscle pain, but the influence of vitamin D on pain in IBD patients is unknown. The aim of this study was to investigate a possible association between vitamin D levels and pain severity in IBD patients. Methods: Participants were recruited from nine hospitals in Norway from March 2013 to April 2014. Clinical data were collected by interview and from medical records. The Brief Pain Inventory (BPI) questionnaire was used to measure pain. To explore the possible association between vitamin D levels and pain severity, linear regression models were fitted. Results: In total, 407 patients were included, 229 (56 %) with Crohn′s disease (CD) and 178 (44 %) with ulcerative colitis (UC). Vitamin D deficiency (25-OH-D < 50 nmol/l) was present in 125 (55 %) of CD patients and 78 (44 %) of UC patients. Pain other than everyday kinds of pain was reported in 182/407 patients (45%), most commonly in the abdomen, back and joints, and was more frequently reported with higher disease activity scores (SCCAI and HBI). In multivariate analysis adjusted for age, gender and disease activity, there was no association between vitamin D levels and pain severity. Higher pain severity scores were significantly associated with female gender in both UC (B 3.06; 95% CI 0.60, 5.53) and CD (B 3.26; 95% CI 1.44, 5.08). There was a trend towards lesser pain severity with 25-OH-D > 75 nmol/l in CD (B −2.42; 95% CI −5.06, 0.23), but not in UC. Conclusions: Pain is commonly reported, followed by more active disease. In this study, female patients reported more severe pain. We found no association between pain severity and vitamin D deficiency, but higher levels of 25-OH-D may influence the experience of pain.